Assessment of cashew species for molecular diversity - ., Thimmappaiah; Gregory Sequeira, Melwyn; Shobha, D.; Raichal Anil, Shirly (Journal of Plantation Crops, 2009)
Genetic diversity in ten accessions of cashew consisting of three wild species, four genotypes of cultivated species and three inter-specific hybrids was studied using RAPD, microsatellite (SSR) and Isozyme markers. Polymorphic bands generated with 11 RAPD primers, six primer pairs of SSR and Isozymes of six enzymes were used for analysis. A total of 151 bands were obtained with 123 polymorphic bands (81.5%) by combining the markers data. High percentage of polymorphism in markers and an average genetic similarity of 54% suggested high genetic variation and moderate diversity existing among the accessions. The Unweighted Pair Group Method with Arithmetic averaging cluster analysis made on genetic similarity grouped the accessions broadly into three major clusters. In these, Anacardium pumilum with its inter-specific hybrids and Anacardium orthonianum with its inter-specific hybrid clustered separately and only Anacardium occidentale clustered with Anacardium microcarpum indicating close affinity between these two species. Even morphologically these two species showed resemblance.